THE EFFECT OF WORKING CAPITAL TURNOVER, COMPANY SIZE, INVENTORY TURNOVER, AND SALES GROWTH OF PROFIT GROWTH (Empirical Study Of Property And Real Estate Sub-Sector Companies Listed On The Indonesia Stock Exchange Period 2018-2021) - Amri, Afifah (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2024)
This research is conducted to analyze the working capital turnover, company size, inventory turnover, and sales growth of profit growth. The population in this study used secondary data on financial reports from property and Real Estate sub- sector companies for the 2018-2021 period which were listed on the Indonesia Stock Exchange (IDX) as many as 46 companies. The research used a purposive sampling method and obtained 33 companies as samples. Data analysis used multiple linear regression analysis with the help of the SPSS version 20 program. The test results showed that working capital turnover had a negative and significant effect on profit growth. Company size and sales growth have a positive and significant effect on profit growth. While inventory turnover has no significant effect on profit growth.